القدرة التنافسية للصادرات السورية في الأسواق الدولية - محمود, حبيب; حمود, ظافر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن الوضع الحالي للاقتصاد العالمي بما ينطوي عليه من الاتجاه المتزايد نحو تحرير الأسواق وإزالة الحواجز والقيود وحرية تدفق السلع والأموال بين الدول يتطلب إيلاء مفهوم القدرة التنافسية للصادرات في الأسواق الدولية أهمية متزايدة من أجل ضمان الاستمرار وسط بيئة دولية شعارها البقاء للأقوى. بناءً على ما تقدم جاء بحثنا هذا ليسلط الضوء على مفهوم التنافسية وتعريفاتها المختلفة, بالإضافة إلى وضع التجارة الخارجية السورية في مجال التصدير. وأخيراً دراسة أهم المؤشرات التي لها علاقة بقياس تنافسية الصادرات كمؤشر الميزة النسبية الظاهرة والتوافق التجاري والتجارة داخل الصناعة ومؤشر تركز الصادرات, من أجل الوصول إلى معرفة تنافسية الصادرات السورية في الأسواق الدولية, وخاصة في الأسواق العربية والاتحاد الأوربي باعتبارهما أهم الأسواق التي تتوجه لها الصادرات السورية. The current situation of the global economy as it involves Highest trend towards market liberalization and removal of barriers and restrictions and the free flow of goods and money between the States requires giving the concept of export competitiveness in international markets increasing importance to ensure continuity in an environment of an international emblem of survival of the fittest. Based on what mentioned above, this study aims to highlight the concept of competitiveness and its definitions as well as various foreign trade situation in the area of the Syrian exports, and finally studying the most important indicators related to measuring the competitiveness of exports as Revealed Comparative Advantage (RCA) and Trade Correspondence Index, and Intra-Industry Trade (IIT), and Export Concentration Ratio , in order to reach knowledge of competitive Syrian exports in international markets, especially in the Arab markets and the European Union as the most important markets to which the Syrian exports are directed.